Special effects spectacle: the technical design effectiveness in musical theatre - Hashim, Hafshizan; Abd Rahman, Khairul Aidil Azlin; Zulkepeli, Mohd Kamil (Primrose Hall Publishing Group, 2020)
Musical theatre production increasingly becomes the focus in the present across Malaysia with the engagement of the diversity of producers internationally. The variety of the factors behind the musical performances indirectly provides traction and lifting uniqueness towards its spectacle's technical effects. Yet, on that point is less attention was exposed through the theatre production process in the context of technical designing of special effects. This is due to the lack of practitioners that lead to researching on technical for theatre in Malaysia. To this end, research on the special effect's invention done is to examine the technical components and approach in resulting impact of visualisation and conceptualisation. The case study on three musical theatre performances at the national theatre of Istana Budaya - Aladdin the Musical (2007), Puteri Gunung Ledang the Musical (2006) and Cats the Musical (2002), is to help in providing guidelines also solutions in the technical design process for theatre performances.